Vivências em um curso de medicina durante a pandemia de COVID-19 - Rodrigues, Amanda Ponce (Universidade Federal de São Carlos)
This final paper aims to report the experiences faced during the Medical graduation course at the Federal University of São Carlos (UFSCar) by a student of the XV class, between 2020 and 2025, focusing on the obstacles caused by the Covid-19 pandemic. The social isolation, whether academical or interpersonal, the fear of contamination and the experience of death and grief were the pillars of this dark times, impacting not only the lives, but also the mental and physical health of many students. Furthermore, the delay in returning to the practical activities, as recommended by the political-pedagogical project of the Medicine Department, and the risks involved in said return, caused great psychic impairment. However, the shared coping of said obstacles, the resilience and the empathy, tools used to build a repertoire of skills to solve problems and manage frustration, were positive and welcomed results of such a terrible historical event. Equipped with these experiences and emotional instruments, I now finish the Medical graduation with the expectation of not having to face such a barrier evermore, and if it so comes to be necessary, then let it be with better strategy and easiness, with greater knowledge, skills and attitudes.
Experiences in a medical school during the COVID-19 pandemic
Keywords: Ensino médico; Pandemia; Isolamento social; Ensino remoto; CIENCIAS DA SAUDE; 3. Saúde e Bem-Estar